Analysis of the Planning Process of Productive Zakat Utilization Programs for Rural Poverty Alleviation - Hurun’in , Siti Zayyini (Journal of Economicate Studies, 2021)
Poverty is a problem that is often faced by many developing countries, including Indonesia. In the Islamic economic system, zakat is one of the socio-economic instruments that is relevant to alleviating poverty so that it can boost national economic performance. In order for zakat to be effective, proper utilization programs are needed so that zakat funds allocated can increase the independence of realizing welfare and bringing mustahik out of poverty. The Center for Zakat Umat (PZU) is an Islamic Union (Persis) Amil Zakat Institution which is dedicated to improving the welfare of the people in the fields of education, health, preaching, social and also economic. In determining the zakat utilization program, PZU has its own program planning model where asnaf in zakat fiqh is interpreted into productive programs that adhere to the rules of the Shari'a. This planning model has given birth to various programs that have been implemented in the PZU working area nationally, one of which is the village program rise. This research uses a case study which is part of a qualitative method that will explore a particular program in more depth by involving the collection of various sources of information.